Anticipatory traveller information system for freeway‐arterial networks. Issue 3 (1st May 2014) - Xu, Tiandong; Hao, Yuan; Peng, Zhongren; Sun, Lijun
Abstract : Anticipatory traveller information system based on variable message sign (VMS) aims to relieve recurrent and non‐recurrent congestion by using predicted traffic conditions to design control strategies consistent with drivers' route choice behaviour to guide drivers through the freeway‐arterial networks and improve system performance. To provide anticipatory traveller information consistent with drivers' en‐route diversion behaviour and controller's objectives effectively, this study examines (i) automated calibration of the parameters of a time‐variant drivers' en‐route diversion model using aggregate‐level data, and (ii) an active route guidance scheme, which projects the network states into the near future and determines spatiotemporal coordinated anticipatory traveller information. The proposed system is tested on real world networks. The implementation results demonstrate that the anticipatory traveller information provided by the proposed model is more consistent, and therefore easier to be accepted by drivers. The findings also reveal that the coordinated VMS‐based anticipatory traveller information effectively provides guidance to drivers because it accounts for the spatial and temporal changes in traffic conditions, and encourages better use of roadway capacity, thereby resulting in better system performance over the same period of operations.